Association between tea consumption and osteoporosis: A meta-analysis. Issue 49 (December 2017) - Sun, Kang; Wang, Le; Ma, Qingping; Cui, Qiaoyun; Lv, Qianru; Zhang, Wenzheng; Li, Xinghui
Abstract: Background: Previous reports have suggested a potential association of tea consumption with the risk of osteoporosis. As such association is controversial, we conducted a meta-analysis to assess the relationship between tea consumption and osteoporosis. Methods and Findings: We systematically searched PubMed, EMBASE and WanFang databases until March 30, 2016, using the keywords "tea and osteoporosis, " without limits of language. Odds ratios (ORs) with 95% confidence intervals (95% CIs) were derived by using random-effects models throughout the analyses. We conducted the analysis of the statistical heterogeneity using Cochrane I 2 . The funnel plot was used to speculate the publication bias, while the subgroup analysis and multiround elimination method were employed. Results: Our study was based on 17 journal articles, including 2 prospective cohort studies, 4 case–control studies, and 11 cross-sectional studies. In the present study, the total OR of osteoporosis for the highest versus the lowest categories of tea consumption was 0.62 (95% CI, 0.46–0.83), with significant heterogeneity among studies ( I 2  = 94%, P  < .01). There was, however, no publication bias of the meta-analysis about tea consumption and osteoporosis. Subgroup analysis showed that tea consumption could reduce the risk of osteoporosis in all examined subgroups. Conclusion: In the present study, it can be concluded from the results that tea consumption can reduce the risk of osteoporosis. Abstract : Supplemental Digital Content is available in the text